Prediction of Cu Zeolite NH3-SCR Activity from Variable Temperature 1H NMR Spectroscopy - Sambhu Radhakrishnan; Sam Smet; C. Vinod Chandran; Sreeprasanth Pulinthanathu Sree; Karel Duerinckx; Gina Vanbutsele; Johan A. Martens; Eric Breynaert (Molecules, 2023)
Selective catalytic reduction (SCR) of NOx by ammonia is one of the dominant pollution abatement technologies for near-zero NOx emission diesel engines. A crucial step in the reduction of NOx to N2 with Cu zeolite NH3-SCR catalysts is the generation of a multi-electron donating active site, implying the permanent or transient dimerization of Cu ions. Cu atom mobility has been implicated by computational chemistry as a key factor in this process. This report demonstrates how variable temperature 1H NMR reveals the Cu induced generation of sharp 1H resonances associated with a low concentration of sites on the zeolite. The onset temperature of the appearance of these signals was found to strongly correlate with the NH3-SCR activity and was observed for a range of catalysts covering multiple frameworks (CHA, AEI, AFX, ERI, ERI-CHA, ERI-OFF, *BEA), with different Si/Al ratios and different Cu contents. The results point towards universal applicability of variable temperature NMR to predict the activity of a Cu-zeolite SCR catalyst. The unique relationship of a spectroscopic feature with catalytic behavior for zeolites with different structures and chemical compositions is exceptional in heterogeneous catalysis.